Estudo de metabólitos secundários de Ruta graveolens como inibidores da fotossíntese - Sampaio, Olívia Moreira (2012)
In this work were isolated eighteen secondary metabolites from Ruta graveolens (Rutaceae), eleven alkaloids (five akridonic, five quinolinics and one quinolonic) and seven furanocoumarins. Thirteen compounds had their herbicide potential evaluated in vitro and in vivo. The inhibitory activity of photosynthesis in vitro was determined by Hill reaction and the active compounds were classified as inhibitors of electron transport and the mechanisms of action were located in the photosystems (PSI and PSII). Studies of chlorophyll a fluorescence in leaf discs of S. oreaceae (semi in vivo) and in plants Lolium pereni (in vivo) confirm the electron transport results. The quantitative analysis parameters of fluorescence`s kinetics were measured and evaluated by energy flows absorbed by PSII antenna system, energy used for QA reduction, energy used for electron transport, and energy dissipation of flow as heat, fluorescence or transferred to other photosystems. In fluorescence in leaf disk, the Plabs parameter showed a decrease of 70% at concentration of 150μM, indicating a stress on the photosynthetic apparatus. Evaluating other parameters, were observed reductions in the PSI0, PHI(E0) and ET0/CS0 and ET0/RC of 40%, 40%, 60% and 40% at 150μM respectively, showing that at low concentrations the effect is intensified for the substance 2-nonyl-N-methyl-4- quinoline. Tests were performed by dry biomass, and the substance 4-methoxy- 7H-furo [3,2-g] chromene-7-one (bergapten) inhibited the growth of grass l. pereni in 20 and 23% at concentrations of 150 and 300μM, acting as postemergent herbicide. The isolated and evaluated compounds can be used as bioherbicides directly or as prototypes of new herbicides for weed control.